(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
The analgesic, anti-inflammatory, anticonvulsant and CNS activities of the ethanolic extract of Butea monosperma roots were examined. The extract produced no significant inhibition of abdominal constrictions caused by acetic acid. It showed significant inhibition of the earlyphase of formalin-induced pain, also reduced the weight of granuloma induced by a cotton pellet. Moreover, the extract caused a moderate inhibition of ear swelling in mice caused by croton oil. In pentobarbital induced sleeping time test the extract slightly reduced the onset and increased the duration of sleeping. Therefore, Butea monosperma showed analgesic, antiinflammatory, mild anticonvulsant activities as well as sedative effect on CNS. Jahangirnagar University J. Biol. Sci. 4(1): 9-18, 2015 (June)